Vitamin D3 status in pre-menopausal and post-menopausal type 2 diabetes mellitus women - Maurya, Jessica; Singh, Naina; Rathore, Hemlata; Gupta, Uma; Rathore, Brijesh (International Journal of Research in Medical Sciences, 2026)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic condition that arises from either total or partial deficiency of insulin. It is a multifactorial disorder characterised by abnormal glucose metabolism, persistent high blood glucose levels, and altered insulin release. Recent study suggest that vitamin D may play a protective role against malignancies, cardiovascular conditions, diabetes, osteoporosis, and various other bone-related diseases. Numerous studies have highlighted a high prevalence of vitamin D deficiency among postmenopausal women, with some suggesting an association with diabetes and metabolic syndrome. Therefore, we aim to assess serum vitamin D3 status in T2DM pre-menopausal and post-menopausal women. Methods: We conducted a cross-sectional study with 104 T2DM pre-menopausal and 104 T2DM post-menopausal women visiting the OPD of Obstetrics and Gynecology. Study population age ranging between 25 to 70 years were recruited and biochemical analysis was done. Results: Mean age (mean±SD) of pre-menopausal and post-menopausal women was recorded as 33.03±5.89 years, and 57.23±8.72 years, respectively. Fasting blood glucose levels in pre-menopausal and post-menopausal women were 199.89±61.69 and 195.09±68.85, respectively, similarly HbA1c values in pre-menopausal and post-menopausal women were 8.70±2.01 and 8.63±2.23, respectively. Serum vitamin D3 levels (mean±SD) were recorded as 43.64±17.91 and 37.08±16.26 in pre-menopausal and post-menopausal women, respectively. A statistically significant (p<0.002) decrease in serum vitamin D3 level was found in post-menopausal women as compared to pre-menopausal women. Conclusions: Results of our study shows statistically significant decrease in serum vitamin D3 levels in post-menopausal T2DM women as compared to pre-menopausal T2DM women.